Habitat selection by large herbivores in a southern African savanna: the relative roles of bottom‐up and top‐down forces. Issue 11 (22nd November 2013) - Burkepile, Deron E.; Burns, Catherine E.; Tambling, Craig J.; Amendola, Elizabeth; Buis, Greg M.; Govender, Navashni; Nelson, Victoria; Thompson, Dave I.; Zinn, Andrew D.; Smith, Melinda D.
Abstract : Animals must often balance food availability and predation risk when selecting habitat. Here, we examined habitat preferences of large mammalian herbivores in a long‐term fire experiment in the Kruger National Park, South Africa to assess the role of bottom‐up (e.g., forage quantity/quality) and top‐down (e.g., predation risk) processes in driving herbivore distributions. We focused on experimental plots (∼10 ha on average) that have been burned in the winter (August) since 1954 at 1‐ and 3‐yr intervals, or left unburned (n = 3 per burn type). Herbivore distributions (during both day and night) and plant community structure were surveyed on each plot during the growing seasons (November–March) of 2005–2006, 2006–2007, and 2007–2008. Overall, we sighted 4, 187 individuals representing twelve species of mammalian herbivores. Impala ( Aepyceros melampus ), zebra ( Equus quagga ), and wildebeest ( Connochaetes taurinus ) comprised 37%, 28%, and 18% of all individuals observed, respectively. Several species such as African buffalo ( Syncerus caffer ), wildebeest, and giraffe ( Giraffa camelopardalis ) exhibited a significant trade‐off between food acquisition and minimizing predation risk by foraging in areas with lower density of woody vegetation. We also observed significant day vs. night dynamics in herbivore habitat selection. For example, zebra utilized annual or triennial burns during the day depending on which years the plots were burned, but they avoided triennial burns with dense woody vegetation in favor of more open annual burns at night when predators such as lions ( Panthera leo ) are more active. Similarly, the smaller, mixed‐feeding impala appeared to use riskier habitats with more diverse forage options during the day (triennial burns and unburned plots) but used less risky habitats at night (annual and triennial burns). Diurnal vs. nocturnal patterns are often overlooked in studies of habitat selection but are necessary for understanding the factors that shape distribution. The variation we observed in herbivore distribution patterns during this three‐year period indicates that different species exhibit different trade‐offs with respect to food and predation risk. Factors such as body size, nutritional requirements, prey escape tactics, and recent fire history likely mediated these interspecific differences.